A life course perspective on childhood adversity, protective factors, and financial fraud vulnerability - Ratzlaff, Brandon DaRell (My University, 2025)
Financial fraud poses a significant threat to individuals’ financial well-being, particularly among older adults who may experience cognitive decline and limited financial decision-making capacity. This study examines how early life adversities (ELAs) contribute to financial fraud vulnerability in later life, with a specific focus on the moderating effects of financial literacy, resilience, social support, and financial guidance. While prior research has linked ELAs to various negative life outcomes, little is known about how early-life adversity influences financial decision-making and fraud susceptibility in adulthood. This study addresses this gap by exploring whether individuals with ELA histories are at greater risk of financial fraud and whether certain protective factors can mitigate this vulnerability. Using data from the Health and Retirement Study (HRS), this study employs quantitative methods, including logistic and linear regression analyses, to examine the relationship between ELAs and financial fraud vulnerability. Multiple imputation techniques are used to address missing data and ensure the robustness of findings. The analysis explores direct effects of ELAs on fraud victimization, as well as the moderation effects of demographic and protective factors. Additionally, the study investigates three-way interactions between ELAs, financial literacy, and psychological resilience to assess whether the combined presence of financial knowledge and behavioral adaptability reduces fraud susceptibility. The findings indicate that ELA exposure is significantly associated with greater financial fraud vulnerability, supporting the life course theory perspective that early-life adversity has long-term economic consequences. However, financial literacy alone does not serve as a protective factor unless paired with resilience, suggesting that financial knowledge must be supplemented with behavioral and psychological adaptability. Among demographic moderators, gender, age, and education significantly influence fraud vulnerability, while race, marital status, and employment status do not. The study also finds that resilience strengthens the protective effects of financial literacy, highlighting the need for financial education programs that integrate both knowledge acquisition and behavioral coaching. These findings have important theoretical, practical, and policy implications. The study extends life course model by demonstrating how childhood adversity creates long-term financial disadvantages, reinforcing the need for early interventions that promote both financial and psychological resilience. Practical implications suggest that financial planners should incorporate trauma-informed approaches when advising clients with ELA histories, while financial educators should design curricula that integrate fraud awareness and behavioral resilience training. Policy recommendations include targeted fraud prevention programs for at-risk individuals and regulatory measures that enhance consumer protections against financial exploitation. By providing empirical evidence on the intersection of ELAs, financial decision-making, and fraud vulnerability, this study contributes to the growing fields of behavioral finance and financial therapy and informs strategies to improve financial security for vulnerable populations.
Keywords: Early life adversity; Financial vulnerability; Life course model; Resilience; Financial literacy; Trauma informed planning